Pembebasan Narapidana melalui Asimilasi dan Integrasi dalam Perspektif Asas Salus Populi Suprema Lex Esto - Akmal, Fathurrahman; Arbani, Tri Suhendra (Universitas Islam Negeri Alauddin Makassar, 2023)
This study examines the substance of the KEMENKUMHAM Decree Number M. Hh-19.Pk.01.04.04 of 2020 in the handling of Covid-19, as well as the relevance of assimilation and integration with the principle of